Perencanaan dan Pengawasan Biaya Operasional PT. Perkebunan Nusantara III Medan Tahun 2016-2022 - Hidayat, Vabella Maharani; Muhammad Arif; Nurwani (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
The research aims to find out the planning and monitoring of operational costs and find out what actions are taken by PT. Perkebunan Nusantara (PTPN) III Medan for the 2016-2022 period in mitigating operational cost inconsistencies. This research uses a qualitative descriptive method with data collection methods in the form of observation and interviews. Based on the research results, it is known that the planning carried out by PTPN III Medan is quite good, the planning is made using a Top Down and Bottom Up approach, the budget is also prepared based on the needs of each division. Supervision is also quite good, with almost no obstacles encountered. The operational cost monitoring mechanism prioritizes the responsibility, trust and honesty of each employee and employees. There are several ways to prevent irregularities in PTPN III Medan's operational costs, namely setting benchmarks for the budget that will be spent on the production process, recording the results of actual implementation and comparing the operational costs incurred with the standards that have been set